Network [videorecording (DVD)] - Lumet, Sidney, 1924-2011; Dunaway, Faye; Holden, William, 1918-1981; Finch, Peter, 1916-1977 (Distributed by Warner Home Video, 2010)
A satirical look at the politics and power struggles of television executives as a network news anchorman turns the tables on the "ratings."